Tourism impacts and sustainability - Cruz, Reil G. (Manila, Philippines : Rex Book Store, 2016)
This book was thus written to address the need for an affordable, easy-to-use, organized, and locally contextualized textbook on the subject. It consists of ten chapters, presented in outcome-based education (OBE) format, with discussion questions, activities, and quiz at the end of each chapter.
Chapter 1. The definition, dimensions, and determinants of tourism impacts -- Chapter 2. Sustainable tourism development -- Chapter 3. Tourism impacts on the environment -- Chapter 4. Tourism impacts on the economy -- Chapter 5. Tourism impacts on culture and society -- Chapter 6. Tourism impact assessment -- Chapter 7. Sustainable tourism practices -- Chapter 8. Managing visitor impacts -- Chapter 9. Tourism impact mitigation -- Chapter 10. Interpretation.
Includes bibliographical references and index.
Keywords: TOURISM -- MANAGEMENT